z/4-6=3

Simple and best practice solution for z/4-6=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z/4-6=3 equation:



z/4-6=3
We move all terms to the left:
z/4-6-(3)=0
We add all the numbers together, and all the variables
z/4-9=0
We multiply all the terms by the denominator
z-9*4=0
We add all the numbers together, and all the variables
z-36=0
We move all terms containing z to the left, all other terms to the right
z=36

See similar equations:

| 15=12x+6 | | k/6+21=28 | | 5/4=y−1/4y= | | q^2−62=-55 | | 8k+6+2k=8+8k | | 7=11x+62 | | q2−62=-55 | | q2−62=–55 | | 8(j-98)=16 | | n2+8=0 | | -2x/5-4=3 | | 4(3x+2)=4(2+3)+4x | | p^2=-71 | | p2=-71 | | 4.75x=2.50x | | -4(3t+1)-7t=5+-4 | | 134=(14+6x) | | 3(3x-5)=33 | | 6x^2+12x+249=0 | | Y2=-8x | | X-(4+4x)=0 | | 3x2+2x+7=0 | | f2=-69 | | 5x+2(x-4)=3x | | 62=7x+11 | | h/2.9h=-8.7 | | Y²=-8x | | -5x-4=0 | | ​(7x​+3)​+(-8x+7=​) | | g/4+15=21 | | 13+9p=49 | | -15=-3(c-1)+9 |

Equations solver categories